Pemetaan dan Penyuluhan Kejahatan Siber di Baubau - Nurul Ahwat Rantekata; La Ode Husaini; Fatimah Suluhu; Wa Una (Lembaga Pengembangan Kinerja Dosen, 2022)
This research and community service aims to provide education to the community about the importance of digital literacy to understand how to use technological tools correctly and not get caught up in cybercrime. In addition, legal explanations are also provided to the community so that they can understand the consequences of cybercrime behavior. The most common cases of cybercrime are online fraud, spreading hoaxes and cyberbullying. It is very easy to commit cybercrime without the victim knowing so that the perpetrators are not afraid and do not deter from repeating the crime. This community service program uses counseling methods such as Community Education and discussion. Stakeholders involved in this counseling are the Baubau City Communication and Information Service, the Baubau City Police, lecturers from the BPI STAI YPIQ Baubau Study Program and students involved in helping the smooth running of the activity. This counseling was carried out for two days and open discussions were held with the community so that the community found a new understanding so that they could prevent and be careful in using technological tools or social media so as not to become victims of cybercrime